The Correlation Between Leukocytosis And Gallbladder Adhesion On Cholecystectomy Patients At X Hospital - Lauwrens, Sabrina Sally; Mellow, Prettysun Ang; Waworuntu, Gladdy L. (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Background: Gallbladder adhesion is a complication which causes difficulty in cholecystectomy. The author aims to seek for a test that could be used as a predictor factor for gallbladder adhesion. In this research, the elevated white blood cell (leukocyte) count is the factor studied. Aim: This study aims to seek for correlation between leukocytosis and gallbladder adhesion on cholecystectomy patients. Method: This research is an observational analytic study using cross sectional design. The independent variable in this research is leukocytosis, and the dependent variable is gallbladder adhesion. Analysis in this research is carried out with Chi-Square test, using a total sampling of 45 medical records of cholecystectomy patients at X Hospital. Result: The majority of cholelithiasis patients in this research were between 50-59 years old (33,3%), with a mean of 51 years old. The number of cholelithiasis patient was dominated by female (62,2%). According to the cholecystectomy procedure, 26 patients underwent laparoscopic cholecystectomy (58,8%). According to clinical presentation, pain in the upper right of the abdomen was experienced by 25 patients (55,6%). Complication suffered by patients was mostly cholecystitis (n=44), yielding the number of 97,8%, followed by gallbladder adhesion in 34 patients (75,6%). Leukocytosis, which is assumed to be the predictor factor of gallbladder adhesion, was found in 15 patients (33,3%). The Chi-Square test showed no significant correlation between the two variable studied (p=0,62). Conclusion: There is no significant correlation between leukocytosis and gallbladder adhesion in cholecystectomy patients.